THU0245 LOW SPECIFICITY OF THE PROPOSED 2017 ACR-EULAR CLASSIFICATION CRITERIA FOR SYSTEMIC LUPUS ERYTHEMATOSUS (SLE) COMPARED TO PREVIOUS CRITERIA IN SLE PATIENTS WITH NEUROPSYCHIATRIC SYMPTOMS. (June 2019) - Monahan, Rory; Beaart, H.J.L.; Gegeneva, Maka; Brilman, E.G.; Beaart- van de Voorde, L.J.J.; Checa, César Magro; Huizinga, Thomas; Steup-Beekman, G.M.
Abstract : Background: New ACR-EULAR SLE criteria have been proposed in order to attempt to improve classification for clinical and translational research (1, 2). Objectives: We evaluated the performance of the proposed 2017 ACR-EULAR classification criteria in a cohort of SLE patients with neuropsychiatric (NP) symptoms and compared to previous classification criteria. Methods: Medical records of patients visiting the NPSLE clinic of the Leiden University Medical Center (LUMC) between 2007-2017 were retrospectively evaluated. The performance of the proposed 2017 ACR-EULAR criteria, the 2012 SLICC criteria and the 1997 ACR criteria was evaluated by calculating sensitivity and specificity. Results: 360 patients were included, of which 294 were clinically diagnosed with SLE. The newly proposed 2017 ACR-EULAR showed a sensitivity of 87% (95% CI: 83-91%) and a specificity of 74% (95% CI: 62-84%), as shown in Table 1 . The 2012 SLICC criteria had a sensitivity of 85% (95% CI: 80-89%) and a specificity of 76% (95% CI: 64-85%). The 1997 ACR criteria had a sensitivity of 89% (95% CI: 85-92%) and a specificity of 89% (95% CI: 80-96%). Sixty out of 294 patients fulfilled the proposed NP domain (delirium/psychosis/epilepsy). Using more specific criteria for NP symptoms related to SLE, as previously proposed by Bortoluzzi et al . (3), only 37 patients fulfilled this domain. However, this did not improve specificity, which remained 74% (95% CI: 62-84%). In addition, the performance of the newly proposed criteria was evaluated including patients with more than 10 points, but negative ANA. This led to an increase of sensitivity to 90% (95% CI 86-94%), but also did not influence specificity. Conclusion: In a cohort of SLE patients with NP symptoms, the proposed 2017 ACR-EULAR classification criteria showed similar sensitivity as the 1997 ACR and the SLICC 2012 criteria, but lower specificity. Including ANA negative patients improved sensitivity. References: [1] 2018ACR/ARHP Annual Meeting Abstract Supplement. Arthritis Rheumatol, 2018.70Suppl 9: p.1-355. [2] Tedeschi SK, et al., Developing and Refining New Candidate Criteria for Systemic Lupus Erythematosus Classification: An International Collaboration. Arthritis Care Res (Hoboken), 2018. 70(4): p.571-581. [3] Bortoluzzi A, et al., Development and validation of a new algorithm for attribution of neuropsychiatric events in systemic lupus erythematosus. Rheumatology (Oxford), 2015. 54(5): p.891-8. Disclosure of Interests: Rory Monahan: None declared, H.J.L. Beaart: None declared, Maka Gegeneva: None declared, E.G. Brilman: None declared, L.J.J. Beaart- van de Voorde: None declared, César Magro Checa: None declared, Thomas Huizinga Consultant for: Merck, UCB, Bristol Myers Squibb, Biotest AG, Pfizer, GSK, Novartis, Roche, Sanofi-Aventis, Abbott, Crescendo Bioscience Inc., Nycomed, Boeringher, Takeda, Zydus, Epirus, Eli Lilly, G.M. Steup-Beekman: None declared